ANALISA PENGARUH PRODUCT IMAGE TERHADAP PURCHASE INTENTION DENGAN TRUST SEBAGAI VARIABEL INTEVENING PADA BLESSCON PT. SUPERIOR PRIMA SUKSES - sherly rosalina (Jurnal Strategi Pemasaran, 2015)
This study aims to analyze the influence of the product image to trust, that impact on purchase intention on Blesscon. This study will be conducted by distributing questionnaires to 100 Blesscon user consumer respondents in East Java. The analysis technique used is the technique of quantitative analysis method path analysis (path analysis) and partial least square (PLS).The research proves that there is a significant influence of the product image to trust on Blesscon, there was a significant effect of trust to purchase intention, and there was a significant effect of product image to purchase intention